Geometric representations of finite groups on real toric spaces - Cho, Soojin; Choi, Suyoung; Kaji, Shizuo (Journal of the Korean Mathematical Society, 2019)
We develop a framework to construct geometric representations of finite groups G through the correspondence between real toric spaces XR and simplicial complexes with characteristic matrices. We give a combinatorial description of the G-module structure of the homology of XR. As applications, we make explicit computations of the Weyl group representations on the homology of real toric varieties associated to the Weyl chambers of type A and B, which show an interesting connection to the topology of posets. We also realize a certain kind of Foulkes representation geometrically as the homology of real toric varieties.
Keywords: Building set; Nestohedron; Poset topology; Real toric variety; Representation; Specht module; Weyl group